The utilization of nursing hours in operating rooms, according to the patient’s complexity and the surgical anesthetic procedure. - De Mattia, Ana Lúcia; Gatto, Maria Alice Fortes (Online Brazilian Journal of Nursing, 2007)
This is a case study with exploratory character, descriptive and comparative, and a fieldwork with a quantitative approach. It aims to classify the surgeries in categories according to the number of nursing hours in operating rooms, subsidizing the dimensioning of the nursing staff in operating rooms. It was performed in a large general private Hospital in São Paulo. The sample was constituted of 140 patients, divided into 14 groups, 10 patients on each group. To organize the groups it was taken on account the patient’s physical condition, according to the American Society of Anesthesiologists (ASA), the anesthetic complexity, according to the Brazilian Medical Association (BMA), the sort of surgical anesthetic procedure: invasive, or minimally invasive (MI) and elective surgeries. According to the patient’s physical condition, groups were constituted with ASA1, ASA2 and ASA3. ASA 4 was put away because there were no cases, and ASA 5 and ASA 6 were put away because they were urgency or emergency surgeries. As to the anesthetic complexity, surgeries were classified as presenting small complexity, mean complexity, large complexity and special complexity. Therefore groups were symbolized as: 1S, 1M, 1L, 1S, 2S, 2M, 2L, 2S, 3M, 3L, 3S, 1SMI, 1MMI AND 2AMI. Data were collect inside the operating rooms, by means of organized observation, according to a guide presenting items referring to the surgery characteristics, human resources, patient’s physical condition and surgical anesthetic procedures. Data analysis was performed according to the surgical patient’s characteristics, hours taken by human resources and by the patient, procedures and material resources employed. In the comparison among groups, the characterization of the surgical patient led to the following results: as to gender, 83 (59,29%) female and 57 (40,71%) male, the higher age frequency was between 30 and 40 years in 34 (24,29%) of the patients. The most frequent surgical specialties were otorhinolaryngology and traumatology in 23 (16,43%), gynecology and obstetrics in 21 (15%) and orthopedics and traumatology in 21 patients (15%). General anesthesia prevailed in 75 (53,58%) of the patients. Concerning the systemic disorders that characterize the ASA, cardiovascular disorders prevailed in 52 (65%) of the patients, 40 (50%) presenting systemic arterial hypertension and 16 (20%) presenting diabetes Mellitus. As to the hours taken, the average hours taken by patients was: 3,40 hours of nursing (NH); 0,10 hours of nurse (NeH); 3,28 hours of nursing assistant (NaH); 6,14 hours of medical staff (MSH); 1,12 hours of surgery (SH), 1,95 hours of operating room (ORH); 0,21 hours of anesthetic preparation (APH) and 0,16 hours of surgery preparation (SPH). For one SH, the average hours taken for each patient was: 3,54 NH; 0,14 NeH; 3,40 NaH; 3,08 MSH and 0,54 SH. Concerning to the procedures taken, the average of invasive procedures was 2,04 and non-invasive procedures 5,70; total procedures 7,74. The average material resources used for anesthesia was 4,19 equipment and for surgery 2,76 equipment; total 6,95 equipment. In the statistical analysis of groups referring to the ASA, according to the anesthetic complexity, results evidenced that small and mean anesthetic complexity presented no significant difference, and were inferior to large and special complexity in variables NH, NaH and MSH; as to the anesthetic complexity according to the ASA the results evidenced that there were almost none difference among the ASA. In the group of minimally invasive surgeries, there was difference only in the material resources, that were superior according to the anesthetic complexity and in the analysis comparing groups of invasive and minimally invasive surgeries with similar anesthetic complexity and ASA the results evidenced that groups of invasive surgeries were significantly inferior in the studied variables in relation to groups of minimally invasive surgeries. Therefore, this study concludes that the NH are related to the anesthetic complexity, and the more complex the anesthetic surgical procedure, the more nursing hours are taken. The relation of NH taken with the patient’s physical condition was not observed. Thus a classification of surgeries in categories was done, according to the necessary nursing hours for one hour of operating room, that is: standard nursing cares, 1,41 hours; complex nursing cares, 1,99 hours and differentiate nursing cares, 1,78 hours.